UNDERSTANDING THE LIVED EXPERIENCES OF DEBT IN UZBEKISTAN: A QUALITATIVE STUDY OF ITS FINANCIAL, EMOTIONAL, AND SOCIAL IMPACTS - Azizbek Ikrom ugli Kurbanov; Prof. Dr. Alfra Sofa, S.T., M.M. (Innovation Science and Technology, 2025)
This study investigates the lived experiences of debt among individuals and small business owners in Uzbekistan, utilizing a qualitative research approach based on semi-structured interviews. In the context of rapid economic liberalization and increased credit access since 2017, the research explores how borrowers perceive, manage, and are aﬀected by indebtedness. Thematic analysis revealed four dominant themes: debt as a pathway to opportunity, emotional and psychological burdens, trust and distrust in fnancial institutions, and the social and familial impacts of borrowing. Findings highlight that debt in Uzbekistan is deeply intertwined with cultural values, family obligations, and perceptions of personal honor, resulting in complex emotional and relational consequences. Moreover, issues of fnancial literacy, institutional transparency, and evolving societal norms play signifcant roles in shaping debt experiences. The study underscores the necessity for enhanced borrower protections, fnancial education initiatives, and culturally sensitive lending practices. It contributes to a deeper understanding of the social dynamics of debt in post-Soviet transitional economies and oﬀers practical insights for policymakers aiming to promote responsible fnancial inclusion.